Cash Transfers after Ebola in Guinea : Lessons Learned on Human Capital - Mavridis, Dimitris; De Walque, Damien (World Bank, Washington, DC, 2022)
This paper evaluates the effects of a program that transferred different amounts of cash to poor households in rural Guinea. The program’s aim was to improve children’s schooling and health outcomes in the immediate aftermath of the Ebola pandemic. In treated villages, households received cash conditional only on attending trainings promoting good health practices and schooling. The program randomized at two levels. The first level was between treated and control villages. The second level was within treated villages. Households were randomly distributed in three treatment arms: (i) no cash transfer, (ii) a cash transfer of 8 USD/quarter/child over two years, and (iii) a cash transfer twice as large as in group (ii). School enrollment increased nationwide and rapidly in the aftermath of Ebola. The authors find that it increased significantly more in treated villages. From a low baseline of around 40 percent of primary-school-age enrollment, treated villages increased their school enrollment by more than 11 percentage points compared to control villages. The effect is higher for larger cash transfers compared to those with no cash transfers in treated villages. School enrollment also increased among untreated households in treated villages, probably due to a combined effect—which cannot be differentiated—from spillovers and from the information campaigns. Despite the massive increase in school enrollment, there is no evidence of effects on learning measures. Health inputs such as vaccination deteriorated overall in Guinea in the aftermath of Ebola, and the program did not mitigate this fall.